Basic investigation of the lectin method for separation and recovery of nucleated red blood cells in maternal blood, and a study into the frequency of nucleated red blood cells in fetomaternal disorders - Ikeya, Miki; Shinya, Masaru; Kitagawa, Michihiro (Congenital anomalies, 2005)
ABSTRACT  We previously reported the separation and recovery of nucleated red blood cells (NRBCs) in maternal blood using the lectin method. In the present study, we verified the lectin method and investigated the appearance of NRBCs during pregnancy. For the concentration of lectin soy bean agglutinin, 7 mL of maternal peripheral blood was collected from 20 subjects, and the relative fluorescence intensity was measured using flowcytometry; 50 mg/mL, used in previous studies, was the optimal concentration. The number of cells recovered at each step of the lectin method was also investigated by FACS using fluorescence‐labeled CD11a and CD33, and the results showed the usefulness of the method. Next, 7 mL of maternal peripheral blood was collected from 292 women with a normal single pregnancy (389 specimens), and NRBCs were separated and recovered using the lectin method. NRBCs slightly increased over the course of pregnancy (y = 4.29x +  5.03, r2 = 0.11). When blood was collected multiple times in the same subjects, NRBCs increased in 63 of 77 subjects (83.1%, percent change: 2.4 ± 19.0). No NRBCs were recovered in 17 subjects (4.7%). Regarding the relationship between fetomaternal disorders and the frequency of NRBCs, 89.4 ± 92.6 cells appeared per 10 mL of maternal blood in the normal group, but NRBCs increased in patients with 18 trisomy, placenta previa, pre‐eclampsia, intrauterine fetal death, and 21 trisomy. NRBC examination may play an assisting role not only in fetal diagnosis but also in fetomaternal diagnosis.